2013
DOI: 10.1007/s10815-013-0087-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers of ovarian reserve and ovarian histology in adult mice treated with cyclophosphamide in pre-pubertal age

Abstract: Purpose AMH is used to quantify the extent of follicular pool in postpubertal women, but its value after chemotherapy is unclear. We tested AMH as a marker of follicular reserve in adult mice treated with cyclophosphamide (CTX) in prepubertal age. Methods Mice received placebo or CTX at age 18 days. AMH and FSH were assessed on day 43, 56, and 95 of life. Ovaries were fixed in formalin, embedded in paraffin, and stained with H&E and TUNEL. Follicular apoptosis was graded. Results All mice exposed to CTX had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…The compounds cross the basal membrane into the granulosa cells around to convert into estradiols and estrones respectively [23,25]. The process is catalyzed by the aromatase enzyme which encoded by the gene CYP19 [23,25], and AMH suppress the expression of aromatase [26,27]. In our research, the patients with PCOS hold a high serum level of testosterone than controls.…”
Section: Discussionmentioning
confidence: 54%
“…The compounds cross the basal membrane into the granulosa cells around to convert into estradiols and estrones respectively [23,25]. The process is catalyzed by the aromatase enzyme which encoded by the gene CYP19 [23,25], and AMH suppress the expression of aromatase [26,27]. In our research, the patients with PCOS hold a high serum level of testosterone than controls.…”
Section: Discussionmentioning
confidence: 54%
“…There is no consensus on whether AMH can be used as a predictor of ovarian function in women undergoing chemotherapy, especially in younger patients [28][29][30]. Although studies have shown that AMH is of little value in predicting ovarian function in underage chemotherapy patients, no reasonable explanation has been found [20,21,28,30]. In our study on healthy women, the AMH level has a persistent trend of decline with ageing in women over 35 years old but remains relatively stable in women younger than 35 years old, which means AMH may not be an accurate and suitable biomarker of ovarian reserve for younger women [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on whether AMH can be used as a predictor of ovarian function in women undergoing chemotherapy, especially in younger patients [28][29][30]. Although studies have shown that AMH is of little value in predicting ovarian function in underage chemotherapy patients, no reasonable explanation has been found [20,21,28,30]. In our study on healthy women, the AMH level has a persistent trend of decline with ageing in women over 35 years old but remains relatively stable in women younger than 35 years old, which means AMH may not be an accurate and suitable biomarker of ovarian reserve for younger women [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…For AMH is relative stable for not been influenced by the menstrual cycle,5 many studies have adopted AMH as a prominent biomarker to assess ovarian function during the post-chemotherapy follow-up period [18,19]. However, the results of those studies were contradictory, and there is no consensus on the predictive value of AMH for ovarian function under chemotherapeutic damage till now [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%